2012
DOI: 10.1002/app.37661
|View full text |Cite
|
Sign up to set email alerts
|

A novel water‐soluble, conducting polymer composite for mild steel acid corrosion inhibition

Abstract: A novel water‐soluble conducting polymer composite, poly(vinyl alcohol‐histidine) was synthesized from aqueous solution by free radical condensation using persulfate. The composite was characterized using UV–Visible, Fourier transform infrared, scanning electron microscopy, thermogravimetric analysis (TG/DTG), and differential scanning calorimetry techniques while its AC conductance was measured by LCZ analyzer. The inhibitive action of the composite on the corrosion behavior of mild steel in 1M HCl was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…With further increase in temperature, inhibition efficiency decreases which indicate the instability of the adsorbed film above 50°C. Similar type results were observed for the other amino acid polyvinyl alcohol composites [16,17]. The increased hydrogen liberation caused the adsorbed polymer film to peel off from the metal surface there by exposing the base metal to acid which is susceptible for the corrosion attack.…”
Section: Effect Of Temperaturesupporting
confidence: 77%
See 2 more Smart Citations
“…With further increase in temperature, inhibition efficiency decreases which indicate the instability of the adsorbed film above 50°C. Similar type results were observed for the other amino acid polyvinyl alcohol composites [16,17]. The increased hydrogen liberation caused the adsorbed polymer film to peel off from the metal surface there by exposing the base metal to acid which is susceptible for the corrosion attack.…”
Section: Effect Of Temperaturesupporting
confidence: 77%
“…Polyvinyl alcohol was reported as a corrosion inhibitor with 50-70 % [11][12][13][14] inhibition efficiency depending on the metal-acid system. In our previous communications polyvinyl alcohol was composited with various amino acids like leucine, histidine, threonine, and cysteine which are reported to have more than 92 % inhibition efficiency in 1M HCl [15][16][17]. The present investigation reports the corrosion inhibition performances of poly(vinyl alcohol-proline) composite.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This group of authors also reported a comparison between the %IE of PVA and PEG (polyethylene glycol) for MS and aluminium corrosion in 0.1 M H 2 SO 4 using gravimetric, hydrogen evolution and thermometric methods and detected that both PVA and PEG displayed practically analogous efficiency [49,74]. Later on, many authors modified the PVA using different substrates the used them as corrosion inhibitors for better performance [75][76][77][78].…”
Section: Polyvinyl Alcohol (Pva) As Aqueous Phase Corrosion Inhibitormentioning
confidence: 99%
“…Mild steel is commonly used in oil and gas production industries among others [1]. One of the major problems in these sectors is the damage caused by corrosion of materials in acidic environments [2].…”
Section: Introductionmentioning
confidence: 99%